2017
DOI: 10.1021/acs.iecr.7b02397
|View full text |Cite
|
Sign up to set email alerts
|

Experiment and Prediction Studies of Marine Exhaust Gas SO2 and Particle Removal Based on NaOH Solution with a U-Type Scrubber

Abstract: Marine diesel engines produce exhaust gas including a lot of SO x and particulate matter (PM), and laws have been promulgated to regulate ship exhaust emissions. This paper proposes a U-type exhaust gas cleaning (EGC) system that is capable of removing SO 2 and particulate matter (PM) simultaneously. The purpose of this study was to find the relationships between removing efficiency and parameters of EGC system, then get the optimal structural and operational parameters. The experimental results show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…However, function (22) does not take the shape factor into consideration; in other words, the optimized scrubber may be too slender (like a pipe) or too wide. According to the existing applications, it is found that D 1 / H 2 can be used to describe the shape factor constraint and its proper range is 0.3–0.6 . Therefore, function (22) is modified as follows: F(bold-italicGenej)={centerexptrue(πD12H24true),0.3D1H20.6andη0.85center0,D1H20.3orD1H20.6orη<0.85…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, function (22) does not take the shape factor into consideration; in other words, the optimized scrubber may be too slender (like a pipe) or too wide. According to the existing applications, it is found that D 1 / H 2 can be used to describe the shape factor constraint and its proper range is 0.3–0.6 . Therefore, function (22) is modified as follows: F(bold-italicGenej)={centerexptrue(πD12H24true),0.3D1H20.6andη0.85center0,D1H20.3orD1H20.6orη<0.85…”
Section: Resultsmentioning
confidence: 99%
“…The reaction of absorption can be simplified as the following chemical reaction equation, which is a pseudo‐first order reaction with a faster rate . The reaction enhancement factor, E , is determined by this function and is expressed by Equation : SO2(aq) + H2O(l) + HCO3(aq)H3O+(aq) + SO32(aq)0.25em + CO2(aq) E=RSO2+RSO32RSO2where R is the molar flux of the species.…”
Section: Optimization Methodsmentioning
confidence: 99%
See 3 more Smart Citations